THE EXPLORATION OF GENRE BASED APPROACH IN TEACHING SPEAKING AT EFL CLASSROOM: A CASE STUDY AT STUDENT HIGH SCHOOL - Kezia Nathalia Graziella; Yogi Setia Samsi; Acep Bahrul Kamil (Academy of Education Journal, 2023)
Speaking is a crucial thing in life and the main form of communication. In this era Indonesia using a "Independence Curriculum" as the leads of the academics. Speaking especially conversation, there will be found many obstacles while learning process or even during the practice of speaking in English. Therefore, this article aims to find out the exploration about the method of "Genre Based Approach" to be the answered of the obstacles while learning speaking English by following the curriculum at EFL classroom. The participants of this research were 10 students with the observation and interview techniques.